SISTEM PAKAR DIAGNOSA GANGGUAN KECEMASAN MENGGUNAKAN METODE CERTAINTY FACTOR BERBASIS WEB - Cindy Febrianti; A. Nurul Anwar (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Anxiety disorder is a mental disorder related to the mind that causes significant and excessive anxiety in patients, accompanied by specific signs and symptoms. Although this disorder is a common mental disorder in society, many people are not aware of its initial onset. The first aspect that may contribute to anxiety is the environment or nearby living place, which can impact how people view themselves, and the second is feeling depressed. When people cannot express their emotions in intimate relationships, anxiety can arise. Physical causes are included in the latter category. Anxiety may result from constant interaction between the mind and body. Based on these problems, an expert system with the certainty factor method is one technique to reduce and help patients with anxiety disorders understand symptoms or causes in the field of technology. This study aims to develop a web-based expert system application to diagnose anxiety disorders based on symptoms experienced by patients (users) using the Certainty Factor method. Diagnostic results will be provided in the form of information and initial solutions for each type of anxiety disorder diagnosed with the disease experienced, which has a percentage value. Based on information collected from experts, as a result of researching to identify anxiety disorders, the system can operate according to its function. And the diagnosis testing of the system based on a collection of patient symptoms can indicate optimal diseases.